Single cell correlation analysis of liquid and solid biopsies in metastatic colorectal cancer - Gerdtsson, Anna S; Thiele, Jana-Aletta; Shishido, Stephanie N; Zheng, Serena; Schaffer, Randolph; Bethel, Kelly; Curley, Steven; Lenz, Heinz-Josef; Hanna, Diana L; Nieva, Jorge; Kolatkar, Anand; Ruiz, Carmen; et al. (Oncotarget, 2019)
As cancer care is transitioning to personalized therapies with necessary complementary or companion biomarkers there is significant interest in determining to what extent non-invasive liquid biopsies reflect the gold standard solid biopsy. We have established an approach for measuring patient-specific circulating and solid cell concordance by introducing tumor touch preparations to the High-Definition Single Cell Analysis workflow for high-resolution cytomorphometric characterization of metastatic colorectal cancer (mCRC). Subgroups of cells based on size, shape and protein expression were identified in both liquid and solid biopsies, which overall displayed high inter- and intra- patient pleomorphism at the single-cell level of analysis. Concordance of liquid and solid biopsies was patient-dependent and between 0.1-0.9. Morphometric variables displayed particularly high correlation, suggesting that circulating cells do not represent distinct subpopulations from the solid tumor. This was further substantiated by significant decrease in concentration of circulating cells after mCRC resection. Combined with the association of circulating cells with tumor burden and necrosis of hepatic lesions, our overall findings demonstrate that liquid biopsy cells can be informative biomarkers in the mCRC setting. Patient-specific level of concordance can readily be measured to establish the utility of circulating cells as biomarkers and define biosignatures for liquid biopsy assays.
Keywords: liquid biopsy; single cell analysis; circulating tumor cells; metastatic colorectal cancer; cytomorphology